The lipid habitats of neurotransmitter receptors in brain - Borroni, Maria Virginia (2016)
Neurotransmitter receptors, the macromolecules specialized in decoding the chemical signals encrypted in the chemical signaling mechanism in the nervous system, occur either at the somatic cell surface of chemically excitable cells or at specialized subcellular structures, the synapses. Synapses have lipid compositions distinct from the rest of the cell membrane, suggesting that neurotransmitter receptors and their scaffolding and adaptor protein partners require specific lipid habitats for optimal operation. In this review we discuss some paradigmatic cases of neurotransmitter receptor-lipid interactions, highlighting the chemical nature of the intervening lipid species and providing examples of the receptor mechanisms affected by interaction with lipids. The focus is on the effects of cholesterol, glycerophospholipids and covalent fatty acid acylation on neurotransmitter receptors. We also briefly discuss the role of lipid phase states involving lateral heterogeneities of the host membrane known to modulate membrane transport, protein sorting and signaling. Modulation of neurotransmitter receptors by lipids occurs at multiple levels, affecting a wide span of activities including their trafficking, sorting, stability, residence lifetime at the cell surface, endocytosis, and recycling, among other important functional properties at the synapse.